A study on factors influence attitude toward credit card usage among employees of Naza World Auto Mall, Petaling Jaya / Nadhirah Mohd Sharif @ Nuri and Mohd Ariff Mohamed - Mohd Sharif @ Nuri, Nadhirah; Mohamed, Mohd Ariff (Faculty of Business and Management, 2014)
This research conducts to study on factors influence attitude toward credit card usage among employees of NAZA World Auto Mall, Petaling Jaya. Specifically, variables such as knowledge about credit card, family influence toward credit card, perception towards credit card and media awareness toward credit card. The first objective of this research is to investigate the factors that contributes to attitude towards credit card usage among employees of NAZA World Auto Mall Petaling Jaya. The second objective is to examine the best relationship between independent variable (attitude toward credit card usage) and dependent variables (knowledge about credit card, family influences towards credit card usage, perception towards credit card usage and media awareness towards credit card. The researchers distributed 161 set of questionnaires on credit card holder in NAZA World Auto Mall, Petaling Jaya. The results show that only independent variable of perception towards credit card has significant relationship with attitude toward credit card usage. The Pearson’s correlation is 0.578 and the p value is 0.000. The other three independent variables do not have significant relationship due to p value more than 0.010.